2020
DOI: 10.1097/md.0000000000018653
|View full text |Cite
|
Sign up to set email alerts
|

Effect of serotonin-norepinephrine reuptake inhibitors for patients with chemotherapy-induced painful peripheral neuropathy

Abstract: Background: To compare the efficacy of serotonin-norepinephrine reuptake inhibitors (SNRIs) treatment for chemotherapy-induced peripheral neuropathy (CIPN) Methods: Two authors independently searched MEDLINE, Embase, Cochran Library, and Web of Science to identify and review articles published from January 1998 until December 2018 according to selection criteria. Outcomes were expressed as mean difference, the pooled odds ratio, or relative risk in a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Due to the incomplete knowledge about the underlying pathophysiology of CIPN, symptomatic treatments have not been consistently successful. It is known that neurotransmitters such as serotonin and norepinephrine are involved in the descending inhibitory nociceptive pathway and can amplify the effects of central sensitization [ 42 ]. Some studies have indicated that serotonin-norepinephrine reuptake inhibitors (SNRI), which inhibit the reuptake of these neurotransmitters and increase synaptic concentrations, can prevent input to the spinal dorsal horn neurons and thereby decrease pain transmission [ 42 ].…”
Section: Pharmacological Strategies For Prevention/treatment Of CImentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the incomplete knowledge about the underlying pathophysiology of CIPN, symptomatic treatments have not been consistently successful. It is known that neurotransmitters such as serotonin and norepinephrine are involved in the descending inhibitory nociceptive pathway and can amplify the effects of central sensitization [ 42 ]. Some studies have indicated that serotonin-norepinephrine reuptake inhibitors (SNRI), which inhibit the reuptake of these neurotransmitters and increase synaptic concentrations, can prevent input to the spinal dorsal horn neurons and thereby decrease pain transmission [ 42 ].…”
Section: Pharmacological Strategies For Prevention/treatment Of CImentioning
confidence: 99%
“…It is known that neurotransmitters such as serotonin and norepinephrine are involved in the descending inhibitory nociceptive pathway and can amplify the effects of central sensitization [ 42 ]. Some studies have indicated that serotonin-norepinephrine reuptake inhibitors (SNRI), which inhibit the reuptake of these neurotransmitters and increase synaptic concentrations, can prevent input to the spinal dorsal horn neurons and thereby decrease pain transmission [ 42 ]. Currently, the only agent that has documented pharmacological activity in the treatment of CPIN is the SNRI, duloxetine [ 43 ].…”
Section: Pharmacological Strategies For Prevention/treatment Of CImentioning
confidence: 99%
See 1 more Smart Citation
“…Along with providing benefit for post-surgical neuropathic pain, both duloxetine and venlafaxine also offer pain relief for patient's suffering from chemotherapy induced peripheral neuropathy [80,81], and even decrease motor neuropathy symptoms [82]. Benefits of these two SNRIs has been their ability to target multiple concerns, such as depression, anxiety, musculoskeletal pain, and neuropathy [83] and thus should be strongly considered as an adjuvant when formulating a comprehensive pain management plan.…”
Section: Antidepressantsmentioning
confidence: 99%
“…The quality of RCTs was assessed using the Cochrane risk-of-bias assessment tool [20]. RCTs without a high risk of bias in any category were considered as good quality studies; RCTs with one high risk or two unclear risks were considered as fair quality studies; and the rest were considered to be poor quality studies [21]. The quality of each nonrandomized and observational study was evaluated using the Newcastle-Ottawa Scale, which evaluates three factors: patient selection (0-4 stars), comparability of the study groups (0-2 stars), and assessment of outcome (0-3 stars) [22].…”
Section: Data Extraction and Study Endpointsmentioning
confidence: 99%